Study of collective beam effects in energy recovery linac driven free electron lasers - Hall, Christopher C., author; Biedron, Sandra, advisor; Milton, Stephen, advisor; Menoni, Carmen, committee member; Fairbank, William, committee member (Colorado State University. Libraries, 2016)
Collective beam effects such as coherent synchrotron radiation (CSR) and longitudinal space charge (LSC) can degrade the quality of high-energy electron beams used for applications such as free-electron lasers (FELs). The advent of energy recovery linac (ERL)-based FELs brings exciting possibilities for very high-average current FELs that can operate with greater efficiency. However, due to the structure of ERLs, they may be even more susceptible to CSR. It is therefore necessary that these collective beam effects be well understood if future ERL-based designs are to be successful. The Jefferson Laboratory ERL driven IR FEL provides an ideal test-bed for looking at how CSR impacts the electron beam. Due to its novel design we can easily test how CSR's impact on the beam varies as a function of compression within the machine. In this work we will look at measurements of both average energy loss and energy spectrum fragmentation as a function of bunch compression. These results are compared to particle tracking simulations including a 1D CSR model and, in general, good agreement is seen between simulation and measurement. Of particular interest is fragmentation of the energy spectrum that is observed due to CSR and LSC. We will also show how this fragmentation develops and how it can be mitigated through use of the sextupoles in the JLab FEL. Finally, a more complete 2D model is used to simulate CSR-beam interaction. Due to the parameters of the experiment it is expected that a 2D CSR model would yield different results than the 1D CSR model. However, excellent agreement is seen between the two CSR model results.
Keywords: coherent synchrotron radiation; ERL; bunch compression; FEL; CSR